Spending from Regulated Retirement Drawdowns: The Role of Implied Endorsement. (8th June 2021) - Alonso‐García, Jennifer; Bateman, Hazel; Bonekamp, Johan; Stevens, Ralph
Abstract: We fielded an online survey in the Netherlands and Australia to explore the influence of an implied endorsement nudge, conveyed by a government‐regulated drawdown from pension wealth, on spending patterns in retirement. The implied endorsement nudge was effective. It influenced the preferred retirement spending patterns of around 30 percent of survey participants, particularly those with fewer financial resources and low pension capability. Australian participants were more likely to follow the nudge where it was framed as implicit government advice, while the Dutch were more likely to respond to a suggestion that the nudge was a recommendation from peers. Our results provide support for a regulated drawdown rule as part of a strategy to guide spending patterns in retirement.